Environmental influences on Aedes aegypti catches in Biogents Sentinel traps during a Californian "rear and release" program: Implications for designing surveillance programs. - Kyran M Staunton; Jacob E Crawford; Devon Cornel; Peter Yeeles; Mark Desnoyer; Josh Livni; Jodi Holeman; F Stephen Mulligan; Nigel Snoad; Scott A Ritchie (Public Library of Science (PLoS), 2020)
As Aedes aegypti continues to expand its global distribution, the diseases it vectors (dengue, Zika, chikungunya and yellow fever) are of increasing concern. Modern efforts to control this species include "rear and release" strategies where lab-reared mosquitoes are distributed throughout the landscape to replace or suppress invasive populations. These programs require intensive surveillance efforts to monitor their success, and the Biogents Sentinel (BGS) trap is one of the most effective tools for sampling adult Ae. aegypti. BGS trap catches can be highly variable throughout landscapes, so we investigated the potential impacts of environmental factors on adult Ae. aegypti capture rates during a "rear and release" program in California to better understand the relative contributions of true variability in population density across a landscape and trap context. We recorded male and female Ae. aegypti catches from BGS traps, with and without CO2, throughout control sites where no mosquitoes were released and in treatment sites where males infected with Wolbachia were released. BGS trap catches were positively influenced by higher proportions of shade or bushes in the front yard of the premises as well as the presence of potential larval habitats such as subterranean vaults. In contrast, an increase in residential habitat within a 100 m radius of trap locations negatively influenced BGS trap catches. For male Ae. aegypti, increased visual complexity of the trap location positively influenced capture rates, and the presence of yard drains negatively affected catch rates in control sites. Lastly, for BGS traps using CO2, higher catch rates were noted from traps placed greater than one meter from walls or fences for both male and female mosquitoes. These results have important implications for surveillance programs of Ae. aegypti throughout the Californian urban environment including adult monitoring during "rear and release" programs.